Pengaruh Net Interest Margin, Loan to Deposit Ratio, dan Non-Performing Loan Terhadap Return On Asset (Studi pada Perbankan yang Listing di BEI) - Adi Bagus Prakoso; Rachma Agustina (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2023)
A healthy bank or not can be measured from the level of profit. If the bank has a profit every year, the bank is still able to maintain its viability. Bank profits can be measured from the Return on assets. This study aims to determine the effect of Net interest margin, Loan to deposit ratio and Non-performing loan on Return on assets in banking companies listed on the IDX in 2019-2021. The sample technique used in this study uses purposive sampling and the number of samples is 54 banking companies listed on the IDX in 2019-2021. The data analysis technique used is the classical assumption test (autocorrelation test), multiple linear regression test, and hypothesis testing. The results of this study indicate that the net interest margin has an effect on return on assets. Loan to deposit ratio has no effect on return on assets. Non-performing loans have no effect on return on assets.